A Review of Analytical Approaches for Detecting Microplastics and Their Degradation Products in Biological and Environmental Samples - Shihad, Arshed AbdAli; Aljabari, Fadhel Ibrahem (American Journal of Biology and Natural Sciences, 2026)
This study investigated the key environmental, socio-economic, and infrastructural factors influencing the current ecological challenges in the target region. Field observations, supported by quantitative and qualitative assessments, revealed significant pressures on natural resources caused by population expansion, weak waste-management systems, and limited regulatory oversight. Soil, water, and air quality indicators demonstrated varying degrees of deterioration, reflecting the cumulative impact of industrial activities, agricultural misuse, and insufficient environmental planning. The analysis further highlighted the absence of long-term sustainability strategies, fragmented institutional coordination, and low community awareness as major obstacles to environmental protection efforts. Statistical interpretation of collected data confirmed strong correlations between anthropogenic activities and the recorded decline in ecosystem performance. A number of targeted interventions were discussed, emphasizing the need to strengthen environmental governance, adopt integrated resource-management policies, and enhance scientific monitoring programs. Overall, the study provides an evidence-based evaluation of current environmental conditions and identifies a set of practical recommendations that can support decision-makers in developing more effective mitigation and adaptation frameworks. These findings contribute to a clearer understanding of the environmental transformations occurring in the region and underscore the urgency of implementing sustainable solutions